P1677KIDNEY ALLOGRAFT HISTOLOGY IN RECIPIENTS WITH TRANSPLANTATION VINTAGE LONGER THAN 10 YEARS. (6th June 2020) - Namba-Hamano, Tomoko; Hamano, Takayuki; Kyo, Masahiro; Yamaguchi, Yutaka; Masataka, Kawamura; Ayumu, Taniguchi; Nakazawa, Shigeaki; Taigo, Kato; Abe, Toyofumi; Kyakuno, Miyaji; Ryoichi, Imamura; Norio, Nonomura; et al.
Abstract: Background and Aims: Few studies have evaluated long-term graft histology. The aims of this study were to reveal the histological characteristics peculiar to long-term graft and to identify clinical manifestations and histological findings predicting graft survival after biopsy. Method: In this retrospective study, we enrolled all allograft biopsies conducted in two institutions between 2002 and 2018 in recipients who had underwent transplantation 10 years before (n=107). The revised Banff criteria were used to evaluate histological findings. For a baseline cress-sectional study, we employed logistic regression analyses, to explore clinical factors associated with each histological parameter. Restricted cubic spline functions were used for non-linear associations. In longitudinal study, log-rank test and Cox proportional hazards models were used to evaluate the death-censored graft loss. Results: Median (IQR) of time after transplantation, recipient age at biopsy, and donor age were 13 (11, 19), 49 (42, 59), and 51 years (43, 58), respectively. Median (IQR) eGFR and proteinuria at biopsy was 29 (24, 40) mL/min/1.73m 2 and 0.46 (0.18, 0.80) g/day, respectively. Seventeen patients (16%) had FSGS lesion, which was the most common glomerular abnormality in this cohort. Figure 1 shows the distribution of histological parameters. Donor age, in addition to proteinuria, was found to be associated with the presence of FSGS lesion [Odds ratio 2.37 (95%CI 1.16-4.88) per 10-year]. When constructing a non-linear model, estimated prevalence of FSGS lesion was increased in grafts from donors of > 40 years old (Figure 2). Logistic regression analyses revealed that eGFR at biopsy and transplantation vintage were associated with the presence of ci [Odds ratio 0.48 (95%CI 0.32-0.71) per 10 mL/min/1.73m 2, and 1.17 (1.05-1.30) per 10-year, respectively]. We also found that eGFR at biopsy and proteinuria were associated with the presence of ct [Odds ratio 0.40 (95%CI 0.26-0.63) per 10 mL/min/1.73m 2, and 2.02 (1.07-3.84) per 1g/day, respectively]. Figure 3 shows Kaplan-Meier curves for death-censored graft survival after biopsy. During 3.5 years of observation, 33% of patients lost their graft functions. Log rank tests revealed that the risk of graft loss is increased in the groups with the presence of ct (p=0.001), and FSGS lesion (p=0.0001), and higher score of cg (p<0.0001). In multivariate Cox proportional hazards model, the highest score of cg in addition to grater proteinuria and lower eGFR at biopsy showed higher risk of graft loss after biopsy [Hazard ratio 3.26 (95% CI 1.25-8.53) as compared to cg0, 1.64 (1.09-2.46) per g/day, and 0.39 (0.24-0.64) per 10 mL/min/1.73m 2, respectively]. Conclusion: The grafts from older donors, especially older than 40 years old, have FSGS lesion more frequently. Only cg score, not ct score or FSGS lesion, predicts graft survival after biopsy in patients with long transplantation vintage, independently from clinical information.